EFFECT OF ACUTE HEAT STRESS ON CIRCULATING TESTOSTERONE LEVEL IN THE WEST AFRICAN DWARF BUCK - EGBUNIKE, G. N.; BITTO, I.O; AKUSU, M.O. (Nigerian Journal of Animal Science, 2023)
The normal levels of circulating testosterone in the West African dwarf back and the influence of season and thermal stress on same were studied in the humid tropics. Animals were fed a maize based concentrate ration supplemented with forage ad libitum and cool clean water was available always. They were housed in a standard goat barn always except when they were exposed to the tropical sun in the paddock for 1 hour for three consecutive rain free days in special cages in the middle of each of the four season. Serum testosterone levels were stable in both the barn the year except in the late rainy season when there was a significant drop (P<0.05) in concentration in both locations. The mean values were 5.05+0.67ng/ml (barn) and 16.89 + 2.22 ng/ml (paddock). With exposure of the bucks to heats stress serum testosterone levels highly significantly (P<0.01) deviated from those of the unexposed bucks by an average of 334.46%- with the increase in the early rainy season being significantly lower (P,0.05) than the other seasons The study indicates that testosterone-dependent physiological processes in the buck under standard management are relatively stable in our environment with season and that undue exposure of the buck to high ambient temperatures could seriously alter the dynamics of androgen metabolism and utilization.